A review of effective-strain based and multi R-ratio crack propagation models and a comparison of simulated results using the two approaches. (January 2021) - Liang, W.; Conle, F.A.; Topper, T.H.; Walbridge, S.
Highlights: Reversal-based damage count model. Effective crack growth data. Multi R-ratio model. Abstract: Several theories and methodologies for running effective-strain and effective-stress based crack propagation models are reviewed. Crack closure behaviour and effective crack growth rate data for various steels were collected and showed that the effective crack growth rate is independent of steel hardness and R-ratio. Crack propagation simulations on a centre elliptical notched specimen were run under constant amplitude and variable amplitude load histories. Two crack propagation models were employed: 1. An effective-strain based model; and 2. A multi R-ratio crack propagation model. A comparison of simulated results from the two models with experimental data shows a good match.